Risk factors and outcomes of anxiety symptom trajectories in type 2 diabetes: the Fremantle Diabetes Study Phase II. Issue 10 (1st July 2020) - Whitworth, S. R.; Bruce, D. G.; Starkstein, S. E.; Davis, T. M. E.; Skinner, T. C.; Davis, W. A.; Bucks, R. S.
Abstract: Aim: To identify determinants and outcomes of 4‐year trajectories of anxiety symptoms in a community‐based cohort with type 2 diabetes. Methods: Some 1091 participants in the Fremantle Diabetes Study‐Phase II with type 2 diabetes completed the Generalized Anxiety Disorder Scale at baseline and biennially for 4 years, in addition to psychological, biomedical and self‐management measures. Latent growth mixture modelling identified trajectories of anxiety symptom severity, and regression models determined predictors of trajectory membership and associated outcomes. Results: Two distinct groups of participants were identified: those with continuously low–no anxiety symptoms (87%) and those with improving but consistently high anxiety symptoms (elevated anxiety; 13%). Higher HbA1c and BMI, macrovascular complications and a history of generalized anxiety and/or major depressive disorder increased the risk of elevated anxiety. Elevated anxiety did not predict change in health‐related outcomes over time. Elevated anxiety and depression symptoms were highly comorbid and those with both displayed the most persistent anxiety symptoms. Conclusions: A subgroup of individuals with type 2 diabetes are at risk of persistently elevated anxiety symptoms. Routine monitoring of the severity of psychological symptoms over time in this population should facilitate earlier and more intensive mood management. What's new?: Screening for anxiety is a recommended part of routine diabetes care, yet the course of anxiety symptoms in this population has not been examined. A subset of individuals with type 2 diabetes are at risk of elevated anxiety symptoms that do not remit over a 4‐year period. High HbA1c, higher BMI and a lifetime history of both depression and anxiety disorders are significant predictors of elevated anxiety. Comorbid depression symptoms are associated with a more persistent pattern of anxiety, and regular screening for both may enable earlier detection and targeted psychological intervention for those at risk.